2022
DOI: 10.1002/pssa.202100711
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Dielectric, and Electrochemical Studies on Poly(Vinylidene Fluoride‐Co‐Hexafluoropropylene)/IonicLiquid 1‐Ethyl‐3‐Methylimidazolium Tricyanomethanide‐Based Polymer Electrolytes

Abstract: Solid polymer electrolyte films blended with ionic liquid 1-ethyl-3-methylimidazolium tricyanomethanide (EMImTCM) and poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) are prepared via solution cast technique. The physical characterization of polymeric film is performed by X-ray diffraction (XRD), polarized optical microscopy (POM), Fourier transform infrared spectroscopy (FTIR), and thermo-gravimetric analysis (TGA) studies. The gel electrolyte film with 300 wt% of IL shows the high ionic conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A slurry of waste peanut shell-derived activated carbon (90 wt%) and binder PVDF (10 wt%) was prepared to prepare electrodes. The prepared slurry was pasted on a graphite sheet ($250 μm) ($1 mg per cm 2 of graphite sheet) and dried in a vacuum overnight at $100 C. A prototype laboratory-scale EDLC supercapacitor is fabricated by sandwiching an already reported ILGPE (PVDF-HFP/EMIM [TCM]) 23 in between the waste peanut shell-derived activated carbon-based electrodes. The EDLC cell is next investigated for its various electrochemical properties using a CHI604D electrochemical workstation.…”
Section: Preparation Of Edlcmentioning
confidence: 99%
“…A slurry of waste peanut shell-derived activated carbon (90 wt%) and binder PVDF (10 wt%) was prepared to prepare electrodes. The prepared slurry was pasted on a graphite sheet ($250 μm) ($1 mg per cm 2 of graphite sheet) and dried in a vacuum overnight at $100 C. A prototype laboratory-scale EDLC supercapacitor is fabricated by sandwiching an already reported ILGPE (PVDF-HFP/EMIM [TCM]) 23 in between the waste peanut shell-derived activated carbon-based electrodes. The EDLC cell is next investigated for its various electrochemical properties using a CHI604D electrochemical workstation.…”
Section: Preparation Of Edlcmentioning
confidence: 99%
“…The cyclic voltammogram of the EDLC was measured at a scan rate of 10 mV/s on a voltage range of −1 to 1V. The usual behaviour of a supercapacitor is indicated by the hysteresis curve of a CV 18 which showed a very remarkable performance with a specific capacitance of 142 F/gm and also the CV plot can be seen mostly rectangular in shape without obvious distortion as shown in Figure 6, indicating that the supercapacitor device is showing ideal capacitive behaviour. Equation (3) was used to compute specific capacitancewhere the “C sp ” is representing the specific capacitance with “i” as the current, “m” is the mass of electrode materials and the scan rate is denoted with “s”.
Figure 6.The CV curve of maximum conducting IL doped PVP polymer electrolyte system.
…”
Section: Device Performancementioning
confidence: 99%
“…∼4×10 5 ) was procured from Tokyo Chemical Industry Co. Ltd. and Sigma-Aldrich, respectively. Ionic liquid incorporated gel polymer electrolyte(ILGPE) was prepared using solution casting technique which was reported earlier by us [30], however, it is brie y described as follows. Firstly, 0.5 gm of PVdF-HFP was dissolved in the appropriate amount of acetone using a magnetic stirrer.…”
Section: Preparation Of Ionic Liquids-based Gel Polymer Electrolytementioning
confidence: 99%
“…Recently, our group reported ionic liquid 1-ethyl-3methylimidazolium tricyanomethanide (EMImTCM) incorporated GPE which offers highest conductivity ∼3.7 ×10 − 2 S cm − 1 at 300% wt. of IL [30]. Hee-Cha et al reported a GPE prepared using the same ionic liquid EMImTCN with copolymer system (PAMPSLi/PVF/emImTCM) which offer ionic conductivity of 5.43 × 10 − 3 S cm − 1 [31].…”
Section: Introductionmentioning
confidence: 99%